Tracking the origin of invasive Rosa rubiginosa populations in Argentina - Hirsch, Heidi (2011)
The exact geographic origin of invasive species populations is rarely known; however, such knowledge is vital to understanding species’ invasion success, spread, and evolution as well as for assessing any biological control options. We investigated the shrub Rosa rubiginosa L., focusing on the presumed European origin of invasive populations in Argentina. We analyzed eight polymorphic microsatellite loci among 102 native (European) and 29 invasive (mainly central Argentinean and Patagonian) populations. Genetic diversity in the invasive range was clearly lower than in the native range, possibly because of a low number of introductions. Contrary to earlier hypotheses, the interpretation of principal coordinate analysis results and Jaccard dissimilarities contradicts the idea of the Argentinean populations having a Spanish origin. Instead, we found a close similarity between Argentinean samples and those from Germany, the Czech Republic, and Austria. We therefore assume that these neighboring countries are the most probable source regions for the Argentinean populations, which in some cases may also have arrived via Chile. According to historic information, emigrants from these regions may have introduced R. rubiginosa to South America in the nineteenth century on at least two occasions, either for food or as rootstock material for propagating living fences.